Analisis Pendapatan Usaha Tani Tanaman Cabai Di Desa Arassie Kecamatan Tiroang Kabupaten Pinrang - Ihmi, Nur; Irmayani, Irmayani; Arman, Arman (Jurnal Agribis, 2024)
The agricultural sector is highly relied upon as one of the pillars in improving the economy of the community, one of which is in Aressie Village, Tiroang District, Pinrang Regency which has quite a lot of agricultural resources, for example, cayenne pepper plants. This study aims to determine the amount of production and the amount of income generated by chili farmers in Aressie Village. This study uses quantitative research types and descriptive quantitative analysis methods generated from questionnaires. The results of the study showed that the average amount of income generated by farmers was 8.5 kg per hectare, and the average amount of production costs required by farmers was IDR 247,141 per hectare. With an average fixed cost of IDR 34,188 and a variable cost of IDR 366,946 and the average income of corn farmers obtained was IDR 187,792,550 per hectare in Tungka Village.